2020
DOI: 10.11591/ijeecs.v19.i1.pp388-394
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of using deep learning algorithms in predicting students achievements

Abstract: <p>Educational Data Mining (EDM)  research has taking an important place as it helps in exposing useful knowledge from educational data sets to be employed and serve several purposes such as predicting students’ achievements. Predicting student’s achievements might be useful for building and adopting several changes in the educational environments as a re-action in the current educational systems. Most of the existing research have used machine learning to predict students’ achievements by using diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 16 publications
1
35
0
4
Order By: Relevance
“…The experiments applied to eight open-source projects show that the proposed model outperforms state-of-the-art defect prediction approaches. Deep learning algorithms utilization in the prediction areas reveals promising results; some of the most recent published articles used CNN and MLP without concentrate on addressing the effectiveness of manipulating the main factors that might have direct influence of the performance of prediction [46], [47].…”
Section: Deep Learningmentioning
confidence: 99%
“…The experiments applied to eight open-source projects show that the proposed model outperforms state-of-the-art defect prediction approaches. Deep learning algorithms utilization in the prediction areas reveals promising results; some of the most recent published articles used CNN and MLP without concentrate on addressing the effectiveness of manipulating the main factors that might have direct influence of the performance of prediction [46], [47].…”
Section: Deep Learningmentioning
confidence: 99%
“…For example, in the study [15], the authors proved that the Deep Dense neural network improve the accuracy of failure-prone student prediction. The convolutional neural network was investigated for the same researching area in [16]. These deep learning techniques were utilized for predicting student final performance in [8] and for predicting students' future development in [17].…”
Section: Related Workmentioning
confidence: 99%
“…The authors announced the good performance of Deep Dense network and also compared the proposed models with other algorithms such as the decision tree algorithm C4.5, random forest, logistic regression and support vector machine. Deep learning models for SAPP problem based on the Long shortterm memory network and convolutional neural network were introduced in [5,20,21]. The results showed that the proposed deep learning models have superior results compared to other tested algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Different methodologies are designed and built to help developers in the refactoring process such as code smells detection strategies [12], logic meta-programming [13], invariant mining [14] and search-based [15,16]. Moreover, machine learning is harnessed in the area of prediction and shows noticeable performance in terms of prediction in various fields as computer vision, defect prediction, natural language processing, code comprehension, bioinformatics, speech recognition, and finance [17][18][19][20][21][22][23][24]. Several machine learning algorithms are utilized in code refactoring prediction at class and method level as well [25,26].…”
Section: Introductionmentioning
confidence: 99%